PENERAPAN SYSTEM E-LEARNING DENGAN EDMODO PADA PENGAJAR UNTUK PENUNJANG SYSTEM PENGAJARAN DI MTSN KELAYAN BANJARMASIN - Rahmadi Agus; Muhammad Edya Rosadi; Suzana Dewi (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2015)
Technological developments, especially in the computer field is now experiencing rapid growth and progress, the data for the company is not just a numbers, words, atapun mark. However merupan softcopy form or file. It is no longer a suggestion, but a requirement for documentation of the data in the form of a database. With the development of these technologies can help all of the activities, ie administration, finance, production, as well as teaching once. One example in the development of technology in the field of teaching, namely e-Learning. E-Learning is a distance learning (distance learning) that utilize computer technology, computer networks and / or the Internet. E-Learning allows the learner to learn through computers in their respective places without having to physically go to follow the lessons / lectures in class. E-Learning often understood as a form of web-based learning that can be accessed from the intranet on a local network or the Internet. Actually, the e-Learning material should not be distributed on-line through a local network or the Internet, distribution off-line using the media CD / DVD also includes a pattern of e-Learning. In this case the application and learning materials are developed according to the needs and distributed through the media CD / DVD, then learners can take advantage of CD / DVDs and learning at the place where he resides.